1985
DOI: 10.1017/s0021932000025098
|View full text |Cite
|
Sign up to set email alerts
|

A study of returning fertility after childbirth and during lactation by measurement of urinary oestrogen and pregnanediol excretion and cervical mucus production

Abstract: Longitudinal studies involving weekly measurement of urinary oestrogen and pregnanediol excretion were performed in 55 post-partum women to identify the patterns of returning fertility. The women kept diaries of breast-feeding episodes, mucus symptoms and times of bleeding; some recorded basal body temperature and acts of intercourse. The study represented a total time of 36 years (7-8 months per woman). The majority of the women were breast-feeding throughout the study. During lactation amenorrhoea, there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…5 During the breastfeeding transition, cervical mucus changes often do not coincide with hormonal variations 6 or with ovulation as confirmed by ultrasound. 7 Temperature measurements may not be accurate in the first cycles after the return of menses, 8 and integrated rules of an NFP method that used mucus and temperature signs showed low specificity and positive predictive value but good sensitivity in predicting the return of fertility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 During the breastfeeding transition, cervical mucus changes often do not coincide with hormonal variations 6 or with ovulation as confirmed by ultrasound. 7 Temperature measurements may not be accurate in the first cycles after the return of menses, 8 and integrated rules of an NFP method that used mucus and temperature signs showed low specificity and positive predictive value but good sensitivity in predicting the return of fertility.…”
mentioning
confidence: 99%
“…9 In addition, there is confusion among users about the interpretation of the natural signs of fertility during the breastfeeding transition, 10 especially if these women have had irregular cycles previously. 11 In studies that have investigated the efficacy of NFP during the breastfeeding transition, 4,6,[11][12][13][14][15][16][17][18] the pregnancy rates at 12 months have ranged from 11.1 13,15 to 24 per 100 women. 16 A more recent study of a new calendar-based NFP method (the Bridge Method), to be used once a woman has had her first menses, determined a pregnancy rate of 11.2 per 100 women over a typical 6-month period of use, 18 but it assumes that women use the lactational amenorrhea method (LAM) before this.…”
mentioning
confidence: 99%
“…Another earlier study by an Australian group found with 55 post-partum breastfeeding women that, after the first menses, 40% had anovulatory ovarian activity, 25% experienced ovulation but with short luteal phases, and 16% had normal ovulations with deficient luteal phases, i.e., luteal-phase lengths less than 11 days. 5 It is clear from the evidence provided by the above studies that there are many (25-40%) deficient (hormonally) and short (by days) luteal phases in the first post-partum menstrual cycle. There also is evidence that the pregnancy rate of women during the first post-partum menstrual cycle is much lower than expected in normal cycling women, i.e., 6-7% compared to 25%.…”
Section: Breast-feeding and Early Pregnancy Lossmentioning
confidence: 94%
“…5 One study was conducted with 276 healthy, premenstrual U.S. women. 6 The researchers found that those women in "stressful jobs" had more than twice the risk of having shorter menstrual cycles than those women in non-stressful jobs.…”
Section: In Depth Stress and Menstrual Cycle Variabilitymentioning
confidence: 99%
“…contraceptives such as the pill, patch, implant, injectable and ring, 15 and even breastfeeding, [16][17][18][19] ECPs may prevent pregnancy by delaying or inhibiting ovulation, inhibiting fertilisation, or inhibiting implantation of a fertilised egg. But, as a comprehensive review of the mechanism of action of levonorgestrel-only ECPs concluded: "At the same time, however, all women should be informed that the best available evidence is consistent with the hypothesis that their ability to prevent pregnancy can be fully accounted for by mechanisms that do not involve interference with post-fertilization events."…”
Section: Introductionmentioning
confidence: 99%